On irregularity strength of disjoint union of friendship graphs - Ali Ahmad; Martin Baca; Muhammad Numan (Electronic Journal of Graph Theory and Applications (EJGTA), 2013)
We investigate the vertex total and edge total modication of the well-known irregularity strength of graphs. We have determined the exact values of the total vertex irregularity strength and the total edge irregularity strength of a disjoint union of friendship graphs.